Tracheobronchitis in patients with diffuse wall thickening: Three case reports. Issue 6 (9th June 2022) - Taniguchi, Hirokazu; Masaki, Yasuaki; Tsuda, Takeshi; Abo, Hitoshi; Muto, Atsushi; Shimizu, Mami; Takata, Naoki; Uchiyama, Akio; Aikawa, Akane; Ishizawa, Shin
Abstract: We herein report the cases of three patients with chest symptoms or fever and diffuse wall thickening of the trachea and main bronchi on chest CT. They were diagnosed with various causes of inflammations of the trachea and main bronchi using bronchial or tracheal biopsy specimens and flexible bronchoscopy. Abstract : More attention should be paid to the wall of the trachea and main bronchi during the interpretation of chest CT in patients with chest symptoms and/or an inflammatory response.